Strategi Pemberdayaan Masyarakat melalui Program PHP2D dalam Pengembangan Komoditas Kopi di Desa Winduaji, Brebes (Studi Kasus Kebun Kopi Winduaji Tahun 2020) - Rizaqi Ruhiyat; Chamid Sutikno; Ariesta Amanda; , Indah Ayu Permana Pribadi; Zaula Rizqi Atika (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
This research is a study in the field of Public Administration aimed at describing community empowerment management through the Holistic Village Development and Empowerment Program (PHP2D) in the development of Kebon Winduaji Coffee in Winduaji Village, Paguyangan District, Brebes Regency in 2020. The research method employed a descriptive qualitative approach with a case study design. The research targets were stakeholders involved in community empowerment activities through the PHP2D program. The selection of informants in this study used purposive sampling technique. Data sources for the research utilized both primary and secondary data. This research focused on aspects including available strengths and opportunities, while simultaneously minimizing weaknesses and threats faced in the development of Kebon Winduaji Coffee. Data analysis used an interactive model with descriptive design. The research findings indicate that successful community empowerment through local products requires a balance between two important elements: preserving local culture and traditions, and adapting to contemporary market demands. The long-term success of community empowerment programs depends not only on the availability of funding and support from various parties. More importantly, it is the ability to build a robust system that can withstand various external changes, while maintaining the distinctive characteristics and authenticity of local products as a sustainable competitive advantage.